Platelet-specific markers are associated with monocyte-platelet aggregate formation and thrombin generation potential in advanced atherosclerosis - Gremmel, Thomas; Ay, Cihan; Riedl, Julia; Kopp, Christoph W.; Eichelberger, Beate; Koppensteiner, Renate; Panzer, Simon (Thrombosis and Haemostasis, 2016)
Platelet activation and thrombin generation are crucial steps in primary and secondary haemostasis. However, both also play major roles in intravascular thrombus formation and therefore in the development of adverse cardiovascular events. In the current study, we first sought to investigate the associations of the platelet biomarkers platelet factor (PF)-4, thrombospondin (TSP)-1, soluble CD40 ligand (sCD40L), and soluble P-selectin (sP-selectin) with each other and with monocyte-platelet aggregate (MPA) formation in 316 patients undergoing angioplasty and stenting. To better understand the interplay between platelet activation and thrombin generation, we subsequently investigated the associations of the platelet biomarkers with thrombin generation potential. The mostly platelet-specific markers PF-4, TSP-1 and sCD40L correlated strongly with each other (all p < 0.001), and the best correlation was observed between PF-4 and TSP-1 (r=0.91). In contrast, sP-selectin, which derives from platelets and endothelial cells, correlated rather poorly with TSP-1 (r=0.12, p=0.04), and did not correlate with PF-4 and sCD40L. While PF-4, TSP-1 and sP-selectin correlated significantly with in vivo MPA formation (all p < 0.001), no such association was found between sCD40L and MPA formation. PF-4, TSP-1 and sCD40L correlated strongly with peak thrombin generation (all p < 0.001) with the best correlation between PF-4 and peak thrombin generation (r=0.55), whereas sP-selectin did not correlate with peak thrombin generation. Likewise, PF-4, TSP-1 and sCD40L correlated significantly with the area under the thrombin generation curve (AUC; all p< 0.01), whereas sP-selectin did not correlate with the AUC. In conclusion, platelet-specific markers are associated with MPA formation and thrombin generation potential in patients with advanced atherosclerosis.
Keywords: Platelet factor-4; thrombospondin-1; soluble CD40 ligand; soluble P-selectin; thrombin generation potential